HASIL PENIALAIAN SEJAWAT SEBIDANG ATAU PEER REVIEW KARYA ILMIAH : JURNAL ILMIAH : The Yudical Review of the Responsibilities of The Company to the Payment of The Money Guarantee the Death of Labor Based on Law Number 24 Year 2011 about BPJS Employment - Dr. Triono Eddy, SH, M.Hum. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
-